2023
DOI: 10.1371/journal.pone.0284100
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing return to work 3 months after percutaneous coronary intervention in young and middle-aged patients with coronary heart disease: A single-center, cross-sectional study

Abstract: Background Today, patients with coronary heart disease (CHD) are becoming younger and younger, and after percutaneous coronary intervention (PCI), most patients want to resume their occupations. The return to work of patients with CHD post PCI in China, however, has received little research attention. So, the goal of this study was to investigate the variables impacting the return to work following PCI in young and middle-aged patients with CHD in Wuxi and to offer a reference basis for the development of targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Another study also revealed that patients with an ejection fraction of <40% tend to have worse self-perceived health, longer RTW, and overall mortality [17]. Meanwhile, Hu et al ( 2023) also presented similar findings where patients with LVEF of j50% exhibited up to twice higher RTW rate than those with lower LVEF [16].…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Another study also revealed that patients with an ejection fraction of <40% tend to have worse self-perceived health, longer RTW, and overall mortality [17]. Meanwhile, Hu et al ( 2023) also presented similar findings where patients with LVEF of j50% exhibited up to twice higher RTW rate than those with lower LVEF [16].…”
Section: Resultsmentioning
confidence: 84%
“…Previous studies have demonstrated that women are less likely to RTW following MI [14][15] [16]. One of the reasons might be that women take on a larger caregiving role within the family [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations